Prevalence Of Migraine Among Headache Patient In Muzaffarabad - Qadeer, Ummara (UNUSA Press, 2021)
Background: Migraine is a most common, progressive and sometimes incapacitating disorder. Symptoms of migraine may include nausea, vomiting, photophobia (sensitivity to light), phonophobia (sensitivity to sound) and usually a short period of visual disruption occur. Objective: To find the prevalence of migraine among headache patient in Muzaffarabad. Methods: Cross-sectional study design, 700 patients with headache were recruited in the study and measured by questionnaire “International classification of headache disorder diagnostic criteria for migraine”. Results: The Prevalence of migraine among headache patient was 40%.Conclusion: It is concluded from the results of this study, that out of 700 studyparticipants 40% (281) participants are suffering from migraine and they wereunaware of this. Keywords: Migraine, Headache